Fake anti-malarials: start with the facts. (December 2016) - Kaur, Harparkash; Clarke, Siȃn; Lalani, Mirza; Phanouvong, Souly; Guérin, Philippe; McLoughlin, Andrew; Wilson, Benjamin; Deats, Michael; Plançon, Aline; Hopkins, Heidi; Miranda, Debora; Schellenberg, David
Abstract This meeting report presents the key findings and discussion points of a 1-day meeting entitled 'Fake anti-malarials: start with the facts' held on 28th May 2015, in Geneva, Switzerland, to disseminate the findings of the artemisinin combination therapy consortium's drug quality programme. The teams purchased over 10, 000 samples, using representative sampling approaches, from six malaria endemic countries: Equatorial Guinea (Bioko Island), Cambodia, Ghana, Nigeria, Rwanda and Tanzania. Laboratory analyses of these samples showed that falsified anti-malarials (<8 %) were found in just two of the countries, whilst substandard artemisinin-based combinations were present in all six countries and, artemisinin-based monotherapy tablets are still available in some places despite the fact that the WHO has urged regulatory authorities in malaria-endemic countries to take measures to halt the production and marketing of these oral monotherapies since 2007. This report summarizes the presentations that reviewed the public health impact of falsified and substandard drugs, sampling strategies, techniques for drug quality analysis, approaches to strengthen health systems capacity for the surveillance of drug quality, and the ensuing discussion points from the dissemination meeting.